What Characterizes a Fast Growing Firm? - Matthias Almus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper seeks to empirically identify factors that influence the probability of beinga fast growingfirm in Eastern and Western Germany. Descriptive analyses have shown that most firms experience only small positive or negative employment growth or stagnate over time. The job generation mechanism rests with a handful of firms that increase their employment significantly over time. The empirical analysis shows that the probability of beinga fast growingfirm depends on different factors when separatingEastern and Western Germany as well as usingdifferen t definitions of fast growingfirms. Moreover, the analysis shows that technology-intensive manufacturing branches and knowledge based business related services do not generate the majority of fast growing firms.
Keywords: O39; C25; L21; 330; New Firms; Fast Employment Growth; Technology orientation; Unternehmensgründung; Unternehmenswachstum; Beschäftigungseffekt; Hochtechnologiesektor; Unternehmensdienstleistung; Schätzung; Alte Bundesländer; Neue Bundesländer; Deutschland